Conservative or Aggressive? The Dynamic Adjustment of the Feed-in Tariff Policy for Photovoltaic Power Generation in China - Fu, Yi; Hu, Chang-hao; Yang, Dong-xiao (Frontiers in Energy Research, 2021)
With the technological progress of photovoltaic (PV) enterprises, the subsidy standard of PV power generation in China is declining. However, the conservative adjustment of Fit-in Tariff (FIT) policy is considered to increase the financial burden of the government, while the aggressive adjustment will have a serious impact on the photovoltaic enterprises, and may reduce the R&D investment of the enterprises. By constructing a game model between the government and PV enterprises, this article analyzes the relationship between the adjustment of government subsidy policy and R&D investment of enterprises, and studies the evolution trend and strategic stability of the system through numerical simulation. Results show that three strategies may become the evolutionary stability strategy (ESS) of the system under certain conditions. However, the comparison of conditions reveals that the probability of strategy that the government chooses conservative adjustment and enterprises choose to increase R&D investment is higher. Secondly, the initial preference of the government and enterprises cannot change the final result of system evolution (RSE), but only changes the speed of reaching it. Finally, the research on the interaction between government and enterprises illustrates that when the degree of influence is small, RSE is that the government chooses aggressive adjustment and enterprises choose to increase R&D investment. However, when the degree of influence is large enough, the government is more inclined to choose conservative adjustment and enterprises choose to increase R&D investment. The government’s decision-making should focus on the interaction between the government and enterprises. Encourage cooperation among PV enterprises, universities and research institutions can promote the technological progress of photovoltaic industry, so as to achieve the purpose of subsidy policies more effectively.